1989
DOI: 10.1111/j.1600-0404.1989.tb03880.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte subsets in human encephalitic and paralytic rabies

Abstract: Lymphocyte subsets of 7 patients with encephalitic and paralytic rabies were determined by immunocytochemical techniques using mouse monoclonal antibodies. Almost all patients had diminished mononuclear cells of Leu 7 phenotype (natural killer cells). Cells of Leu 12 marker (B cells) were decreased in 3 paralytic rabies patients compared with those of 4 patients in the encephalitic group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…We have shown that some paralytic rabies patients may lack the ability to produce antibody as evidenced by diminished circulating B cells and IL-6 levels. Fewer paralytic rabies patients had rabies-neutralizing antibody in the sera [14,42].…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that some paralytic rabies patients may lack the ability to produce antibody as evidenced by diminished circulating B cells and IL-6 levels. Fewer paralytic rabies patients had rabies-neutralizing antibody in the sera [14,42].…”
Section: Discussionmentioning
confidence: 99%
“…Mainly in MS, the distribution of leukocyte subsets both in the cerebrospinal fluid (CSF) and in the peripheral blood (PB) has been widely investigated with monoclonal antibodies, (2)(3)(4)(5)(6), while, as pointed out by McFarlin (7), to date relatively few studies have been focused on CNS I D (8)(9)(10)(11)(12), nor on the two diseases simultaneously (13,14).…”
mentioning
confidence: 99%
“…Evidence of cellmediated immunity, by lymphocyte transformation tests, was found in six of nine furious encephalitis patients, but not in seven with paralytic disease (Hemachudha et al 1988), who had few B cells. Both groups had reduced NK cell levels (Sriwanthana et al 1989). …”
Section: Immunologymentioning
confidence: 99%